THE SYNERGY OF ECONOMIC GROWTH, INCOME INEQUALITY, AND POVERTY IN THE CITY OF SURAKARTA - Suryanto, Suryanto (EP FEB UNS, 2020)
Economic growth is one of the conditions to improve the quality of life of an area. The impro-ved quality of life is marked by the level of income, level of education, and an increased degree of health as well. But the goal of improving people's quality of life is not easy. The purpose of this study is to analyse the relationship between economic growth, income inequality, and pov-erty that occur in the city of Surakarta. The results of the analysis will provide an overview for policy makers to be able to improve synergy between development programs, between gov-ernment service organizations (OPD), and also coordination between government officials. The analytical method used was quantitative descriptive method. The data used were second-dary data obtained from Bapppeda and BPS. Correlation analysis was used to get the relati-onship between variables. The conclusion was Surakarta City's economic growth has shown good performance and inflation could be controlled. However, the income inequality tended to increase even though the number of poor people had decreased from year to year. Keywords: Inequality of income, poverty, economic growth,JEL Classification:O44, E62, I32